Front to back ocular injury from a vaping-related explosion - Khairudin, Muhammad Najmi (BMJ Case Rep, 2016)
We describe a case of extensive ocular injury secondary to an electronic cigarette (e-cigarette)-related explosion. The explosion was the result of modifications made to a heating element of the e-cigarette device by a non-professional. Extensive ocular injuries that result from an explosion of an e-cigarette device can potentially cause significant and permanent visual impairment.